Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2) Vertical Transmission Covid-Positive Mothers in Neonates - Maryam Najam, Rizwana Tareen, Nighat Jabeen, Maryam Rafiq Ghuncha, Muhammad Saqib Habib, Ammara Farooq, Muhammad Hamza (Pakistan Journal of Medical & Health Sciences, 2023)
An outbreak of Covid-19 occurred in Wuhan, China initially in December 2019. Over the next few months, the wide spread of SARS-CoV-2 had been reported in all continents and the transmission in utero from an infected mother to fetus debating yet was observed.1,9 Objectives: To determine risk of vertical transmission of corona virus in neonates of SARS COVID-2 positive mothers. Study Design: A Cross-Sectional study. Place and Duration of Study: Pediatric department of Pakistan Air Force (PAF) Hospital, Islamabad, Pakistan. The study conducted during 01-03-2020 to 31-08-2020. Results: Total 14(87.5%) out of 16 COVID positive mothers were asymptomatic. 16(100%) neonates were negative for Sars-COV-2 at 24 hours and 48 hours. Conclusion: This study concluded with no evidence of transmission of COVID-19 from infected mothers. Keywords: Vertical transmission, COVID-19, neonate, infected mother.